Characteristics and nutrient profiles of foods and beverages on online food delivery systems - Chin, Jia Wen; Loh, Wendy Mei Ling; Ooi, Yasmin Beng Houi; Khor, Ban Hock (British Nutrition Foundation, 2025)
Recently, there has been an emerging trend of purchasing foods and beverages via online food delivery systems but there is scarce evidence on the healthfulness of these items, particularly in Southeast Asian countries such as Malaysia. This study aimed to evaluate the characteristics and nutrient profiles of foods and beverages available via online food delivery systems in Malaysia. This cross-sectional study was conducted from September 2022 to March 2023 to identify foods and beverages available on the Grab Food and Foodpanda mobile applications. The healthfulness of selected foods and beverages was determined based on the Food Standards Agency Nutrient Profiling System. The present study included 3729 foods and 1882 beverages. Most of the foods were cereal-based dishes (37.4%), followed by cereals with protein-based dishes (12.8%) and meat or poultry-based dishes (12.0%), while most of the beverages were local handcrafted beverages (27.8%), followed by bubble milk tea (15.0%) and Western handcrafted beverages (14.6%). For protein dishes, deep-frying or battered-frying was the most common preparation method (33.8%) while most of the cereal-based dishes were stir-fried (76.7%). Out of 23 common foods, 15 foods (65%) were categorised as less healthy based on the nutrient profile score while 19 out of 24 (79%) common beverages were categorised as less healthy. The online food delivery systems feature predominantly local foods and beverages that are less healthy, potentially contributing to the development of an obesogenic environment.